Homozygous mice with mutant protein FUS[1-359] overexpression: Innovative possibilities for ALS treatment - Nikita S. Zhunusov (Research Results in Pharmacology)
Introduction: This study investigates a mouse model with overexpression of the mutant FUS[1-359] protein, which can be used to evaluate the effectiveness of gene therapy and other pharmacological interventions for amyotrophic lateral sclerosis (ALS). The model enhances the deeper understanding of the mechanisms underlying disease progression and allows for testing new therapeutic strategies.